Systems Analysis in Nutrition and Health Planning: Approximate Model Relating Birth Weight and Age to Risk of Deficient Growth - Stickney, Robert E. (1976)
This paper summarizes the initial phase of an effort to develop semiquantitative methods for nutrition and health planning. The general approach is to utilize the methods of systems analysis and operations research where appropriate, but the emphasis is on developing a simplified, approximate analysis that government planning groups could conveniently apply in evaluating various potential programs for attaining specific nutrition and health objectives, while satisfying certain constraints (e.g., budget, facilities, personnel). An essential element of the analysis is a model that provides an approximate description of malnutrition (inadequate growth, as indicated by weight for age) and mortality in terms of those variables that can be affected by intervention programs. We have concentrated initially on using the results of two INCAP longitudinal studies to develop models relating the incidence of malnutrition (second and third degree on the Gomez scale) to age and previous growth, including birth weight. The two studies cover rural Guatemalan communities with considerable variability in ethnic, socioeconomic, and ecological conditions. Because they are tentative, the resulting models are discussed only qualitatively and not quantitatively. The models may serve as baselines to estimate the consequences of potential programs aimed at different target groups, such as pregnant women and children whose weights at birth or thereafter fall below prescribed levels. The possible benefits of using models of this nature in nutrition and health planning are discussed.